To Stay or Leave?: Consequences of Ethical Dilemma Experienced by Nurses in the Intensive Care Units - Kalaycioglu, Ozan (Journal of business ethics, 2025)
Global shortages of healthcare workers, particularly nurses, have been exacerbated by the COVID-19 pandemic, putting significant pressure on healthcare systems worldwide. According to the International Council of Nurses (ICN), 13 million additional nurses are urgently needed to meet global demand. Nurses, who are the backbone of patient care, have faced unprecedented ethical dilemmas, particularly in intensive care units (ICUs), where resource allocation, such as ventilator management and triage decisions, often conflict with basic ethical principles. This study seeks to contribute to the literature by examining the effect of the ethical dilemmas experienced by ICU nurses during COVID-19 pandemic on emotional exhaustion and turnover intention and testing whether emotional exhaustion has a mediating role on the relationship between ethical dilemma and turnover intention. The research model was tested with partial least square structural equation modeling (PLS-SEM) in the package program SmartPLS. The bias-corrected bootstrapping (resampling) method was applied to the sample of 189 nurses who work in the intensive care units in the hospitals in the East Black Sea Region of Türkiye. The research results indicated that ethical dilemma is positively associated with emotional exhaustion (β = 0.305, 95% CI [0.167-0.407]), and turnover intention (β = 0.156, 95% CI [0.146 - 0.423]). In addition, emotional exhaustion has a complementary partial mediation effect (B = 0.149, 95% CI [0.083-0.215]) between ethical dilemma and turnover intention among ICU nurses.